2002
DOI: 10.4049/jimmunol.168.4.1590
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Myeloid Translocation Gene 16b as a Novel A Kinase Anchoring Protein in T Lymphocytes

Abstract: Increased levels of intracellular cAMP inhibit T cell activation and proliferation. One mechanism is via activation of the cAMP-dependent protein kinase (PKA). PKA is a broad specificity serine/threonine kinase whose fidelity in signaling is maintained through interactions with A kinase anchoring proteins (AKAPs). AKAPs are adaptor/scaffolding molecules that convey spatial and temporal localization to PKA and other signaling molecules. To determine whether T lymphocytes contain AKAPs that could influence the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 42 publications
4
52
0
Order By: Relevance
“…A recent report of overexpression of RII␣ in an RII␣-deficient B lymphoid cell line (Reh) indicated a regulatory role for Golgi-associated PKA in transport of ricin, a plant toxin, from endosomes to Golgi (31). Two other Golgi-localized AKAPs, myeloid translocation gene 16b (32) and AKAP350 (33), have also been described.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report of overexpression of RII␣ in an RII␣-deficient B lymphoid cell line (Reh) indicated a regulatory role for Golgi-associated PKA in transport of ricin, a plant toxin, from endosomes to Golgi (31). Two other Golgi-localized AKAPs, myeloid translocation gene 16b (32) and AKAP350 (33), have also been described.…”
Section: Discussionmentioning
confidence: 99%
“…8,20,21 It has been shown that AKAP75 overexpression inhibited smooth muscle cell proliferation in vitro and in vivo by inducing cyclin-dependent kinase-2 inhibitor p27 kip1 . 9,22 Moreover, an increased level of intracellular cAMP inhibited T cell proliferation 10,11 and induced apoptosis in cancer cells. 13,[23][24][25][26][27] The effect on the proliferation of ovarian cancer cells of the agents such as taxanes in augmenting AKAP3 mRNA expression should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, it has been demonstrated that AKAP-mediated PKA activation inhibited cell growth in the muscle 9 and T lymphocytes. 10,11 Paclitaxel, docetaxel and vincristine, which were shown to damage microtubules, also activate PKA and induce hyperphosphorylation of Bcl-2, cause growth arrest and apoptosis. 12,13 Chemotherapy using a paclitaxel-based regimen is now commonly used for the treatment of postoperative ovarian cancer patients.…”
mentioning
confidence: 99%
“…Small GTPases have GTP hydrolysis activity, thereby working as molecular switches that are functional in the GTP bound form and turned-off in the GDP bound form. GTP bound GTPases preferentially associate with downstream effectors such as Rho kinase (ROCK), p21-activated kinase (PAK), phosphatidylinositol-4-phosphate interact with Nervy/MTG family proteins, which among other roles have been found to function as protein kinase A (A kinase) anchoring proteins (AKAPs) 25,26 and link protein kinase A (PKA) to the Plexin A receptor (Fig. 1A).…”
Section: Small Gtpases Are Key Regulators Of Cytoskeletal and Adhesivmentioning
confidence: 99%